Makna Komunikasi Antarpribadi dalam Upaya Pemeliharaan Kesehatan Mental di Kalangan Remaja - Tasya Pratiwi Aisyah; Anne Maryani (UNISBA Press, 2024)
Abstract. Most adolescents experiencing mental health issues greatly need someone as their support system. Besides access to assistance services and counseling, the role of the surrounding environment, such as friends, is crucial in maintaining mental health disorders. This study aims to understand the meaning of interpersonal communication that can arise through individual experiences, the role of support from the surrounding environment, and the individual's internal motives in maintaining mental health. This research uses a qualitative method with a constructivist paradigm and a phenomenological approach. The theory employed in this study is Alfred Schutz's phenomenological theory. Interviews, observations, documentation, and literature studies are the data collection techniques used in this research. The data analysis technique used in this study follows the Miles and Huberman model, which consists of data reduction, data presentation, and conclusion drawing. The results of this study indicate that interpersonal communication experiences of students who have experienced mental health disorders with their surroundings are triggered by personal issues within the students. Students who have experienced mental health disorders tend to become more open to their surroundings after consulting with a psychologist. Moreover, the surrounding environment plays a very important role in maintaining the mental health of these students because the positive feedback they receive leads to effective communication. Additionally, In-Order-To Motive and Because Motive also serve as triggers in forming the meaning of communication for the experiences of students who have experienced mental health disorders and then have the courage to consult a psychologist. Abstrak. Sebagian besar remaja yang mengalami masalah kesehatan mental sangat memerlukan seseorang sebagai support system mereka. Selain akses layanan bantuan dan konseling, peran lingkungan sekitar seperti teman sangatlah penting dalam upaya pemeliharaan gangguan kesehatan mental. Penelitian ini bertujuan untuk mengetahui makna komunikasi antarpribadi yang dapat timbul melalui pengalaman individu, adanya peran pendukung dari lingkungan sekitar, dan motif dalam diri individu guna memelihara kesehatan mental. Penelitian ini menggunakan metode penelitian kualitatif dengan paradigma kontruktivis serta pendekatan fenomenologi. Teori yang peneliti gunakan dalam penelitian ini ialah teori fenomenologi Alfred Schutz. Wawancara, observasi, dokumentasi, dan studi pustaka merupakan teknik pengumpulan data yang peneliti gunakan pada penelitian ini. Adapula teknik analisis data dalam penelitian ini menggunakan model analisis data Miles dan Huberman yang terdiri dari reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini adalah, pengalaman komunikasi antarpribadi mahasiswa yang pernah mengalami gangguan kesehatan mental dengan lingkungan sekitarnya dipicu oleh adanya suatu masalah dalam diri mahasiswa. Mahasiswa yang pernah mengalami gangguan kesehatan mental cenderung mulai terbuka dengan lingkungan sekitarnya setelah melakukan konsultasi dengan psikolog. Adapula lingkungan sekitar memiliki peran yang sangat penting bagi pemeliharaan kesehatan mental mahasiswa tersebut karena feedback positif yang mereka dapatkan menimbulkan komunikasi yang efektif. Selain itu, In-Order-To Motive dan Because Motive juga menjadi pemicu dalam pembentukan makna komunikasi bagi pengalaman mahasiswa yang pernah mengalami gangguan kesehatan mental dan kemudian memberanikan diri untuk melakukan konsultasi ke psikolog.